The characterisation of a novel Xanthomonas Bacteriophage - Petersen, Yolanda (Department of Biological Sciences, 2023)
During the 1994-95 growing season, an apparently new disease was observed on Brassica oleracea var. capitata (cabbage) seedlings in nurseries of the province of KwaZulu-Natal, South Africa. Named chocolate spot disease of crucifers because of the characteristic symptoms of dark brown to black lesions with transparent centers, this disease was particularly severe on the more mature leaves of stressed seedlings and resulted in serious economic losses. The causal agent, determined to be a strain variant of Xanthomonas campestris pv. campestris was found to be associated with bacteriophage-like particles. The optimal growth conditions for production of the bacteriophage-like particles by the chocolate spot pathogen were determined and a purification protocol developed that yielded particles in a quantity and quality adequate for further analysis. Based on a comparison of the particle and bacterial protein reactions with the antiserum raised against the purified particles, it was concluded that the particles were not vesicles originating from the bacterial membrane, but were therefore most probably of bacteriophage origin. Physicochemical characterisation showed that the putative phage is a tailless isometric particle with a diameter of 33.45 nm, sedimentation coefficient of 85S and a density in CsCl of 1.347 g/ml. The phage is relatively stable with respect to pH, solvents and at temperatures of 40°C and 60°C. The particles contain 3 major proteins of 94, 32 and 21.8 kDa as well as two minor proteins of 40 and 25.7 kDa, and it has a single-stranded DNA genome. Biological characterisation of the novel bacteriophage indicates that it is a temperate phage which does not cause visible plaque formation on solid media and is not inducible by the external factors, mitomycin C and ultraviolet radiation. Serological tests showed that the phage is present in all isolates of the chocolate spot pathogen and that similar particles are associated with the X. campestris pathovars aberrans, armoraciae, campestris and raphani. No serological relationship was detected between the novel phage and the X. c. pv. campestris phage, RR68. However, the novel phage antibodies recognised 3 proteins of molecular weights 21.8, 13.79 and 12.64 kDa in the X. c. pv. campestris phage, HT3h. These proteins are localised in the phage capsid. Although phage-like particles were detected in the novel phage host PCB 22 following electron microscopy of ultra-thin sections, immunogoldlabelling could not confirm whether the particles were of phage origin. The single-stranded DNA genome of the phage hybridised with a 53.9 kb extrachromosomal DNA element. Since its size precludes this element being packaged as single-stranded DNA into a capsid 33.45 nm in diameter, it is most probable that this 53.9 kb DNA element is an indigenous plasmid into which the double-stranded form of the phage genome has integrated. However, this could not be confirmed by the results of the nucleic acid hybridisation tests. The 53.9 kb extrachromosomal element was cloned and several recombinant plasmids sequenced. No typical phage genes were identified. However, fragments of a Xanthomonas avirulence (avr) gene interrupted by part of a transposon sequence were identified. A 201- 262 base region of clone pSSI shared a 98% identity to the 3' end of a group of Xanthomonas avr genes, while 141-311 bases had a high degree of nucleotide similarity to the 5' end of the avr genes. These two regions of avr gene similarity which appear to converge, are interrupted by 1259 bases sharing 99% nucleotide identity to the 4864-6126 bp position of the 6938 bp X. campestris transposon, ISXC5 and 298 bases with 97% similarity to the 6644-6938 bp region of the transposon. The 1259 and 298 base regions are in tum separated by an unsequenced region of 518 bases. The presence of the avr and transposon sequences (usually located on plasmids or the bacterial chromosome) on the extrachromosomal element strengthens the hypothesis that the phage genome is integrated into an indigenous plasmid.